Optimization of Zakat Management Based on Ethereum Blockchain and Its Impact on Cost Efficiency - Ardhiyansyah, Ilham; Furqon, Ahmad; Mashilal, Mashilal (Faculty of Economics and Management, 2025)
Zakat is a fundamental component of Islamic social finance, intended to reduce inequality and strengthen community welfare. However, traditional zakat systems face recurring issues, including inefficiency, lack of transparency, and low public trust. This study aims to optimize zakat management using Ethereum blockchain technology, particularly the Layer 2 (Base) network, with a focus on its impact on cost efficiency and system transparency. Using a qualitative-descriptive approach, the research designs and simulates a blockchain-based zakat distribution model that incorporates smart contracts for automated fund allocation to eight categories of ashnaf, along with off-chain verification for Sharia compliance. A simulation of USDC 1,000 zakat fund distribution demonstrates that the blockchain system ensures accurate, traceable, and tamper-proof transactions, while reducing transaction costs by over 98% compared to conventional methods. Smart contracts automate the disbursement process, while all transaction records are stored on a public ledger, which supports real-time auditing and enhances institutional accountability. These results demonstrate that the integration of blockchain technology not only improves operational efficiency and transparency but also supports Islamic legal and ethical governance. In conclusion, this model provides a practical and scalable framework for modernizing zakat management with a strong emphasis on cost efficiency, public trust, and Sharia compliance.